Evaluating Ecological and Economic Benefits of a Low-Carbon Industrial Park Based on Millennium Ecosystem Assessment Framework. (18th December 2012) - Chen, Bin; He, Guoxuan; Yang, Jin; Zhang, Jieru; Su, Meirong; Qi, Jing
Abstract : The Millennium Ecosystem Assessment (MA) framework was modified with a special focus on ecosystem service values. A case study of a typical low-carbon industrial park in Beijing was conducted to assess the ecological and economic benefits. The total economic value of this industrial park per year is estimated to be 1.37 × 10 8 RMB yuan, where the accommodating and social cultural services are the largest two contributors. Due to the construction of small grasslands or green roofs, considerable environmental regulation services are also provided by the park. However, compared with an ecoindustrial park, carbon mitigation is the most prominent service for the low-carbon industrial park. It can be concluded that low-carbon industrial park construction is an efficacious way to achieve coordinated development of society, economy, and environment, and a promising approach to achieving energy saving and carbon reduction.